The li lineage of traditional chinese medicine - Heng Li (Wolters Kluwer Health/LWW, 2019)
Professor Li Ding (李鼎) is the founder and tenured professor, doctoral supervisor at Shanghai University of Traditional Chinese Medicine, a Representative Inheritor for China Intangible Cultural Heritage - Acupuncture and Moxibustion. It is well known that Chinese medicine is rooted in Chinese culture and history. The inheritance of Chinese medicine cannot be separated from the inheritance of Chinese culture and history. Professor Li Ding's path of Chinese medicine inheritance perfectly reflects the above-mentioned laws and is worthy of further exploration and research. The full text of this article is divided into three parts and will be published one after another. The first part "The Lineage of Gu Yi Tang" brings us Li's family historical stories; the second part "The Lineage of Chinese Studies" introduces professor Li's Chinese culture studies; and the third part "The Lineage of Dao Sheng Tang" discusses professor Li's inheritance of Chinese medicine. This article will bring our readers a rich and colorful Chinese scroll painting, which not only focuses on Chinese Medicine, acupuncture but also touches ancient Chinese history, culture, Daoism, and even more.